P2.021 Prevalence of Sexually Transmitted Infections in Young People in St. Petersburg, Russia, as Determined Using Self-Collected Non-Invasive Specimens. (13th July 2013) - Shipitsyna, E; Khusnutdinova, T; Ryzhkova, O; Krysanova, A; Grigoryev, A; Ryzhikh, P; Guschin, A; Savicheva, A; Unemo, M
Abstract : Background: Young people are worldwide a risk group for sexually transmitted infections (STIs) and a primary target for screening. Knowledge on STI prevalence in the youths is essential to elaborate preventive measures. Self-sampling has been shown to be an effective approach in screening and epidemiological programmes. This study aimed to assess the prevalence of Chlamydia trachomatis, Neisseria gonorrhoeae, Mycoplasma genitalium and Trichomonas vaginalis in young people in St. Petersburg, Russia using self-collected non-invasive specimens. Methods: In total, 1207 consecutive sexually active attendees (1053 female and 154 male) of the youth centre Yuventa in St. Petersburg, Russia, aged 15–25 years and consenting to participate, were enrolled in the study from June through November 2011. The mean age of the women was 20.2 ± 2.8 years, and the men 20.2 ± 2.9 years. Vaginal and male urine samples were self-collected using Self-Collection Specimen Kit (Central Research Institute for Epidemiology, Russia) and UriSWAB (Copan, Italy), respectively. Testing for the STIs was performed by multiplex real-time PCR (AmpliSens N .gonorrhoeae/C.trachomatis/M.genitalium / T.vaginalis -MULTIPRIME-FRT, Central Research Institute for Epidemiology). Results: The overall prevalence of the examined STIs was 8.1% (85 of 1053) in the women and 7.8% (12 of 154) in the men. C. trachomatis, N. gonorrhoeae, M. genitalium and T. vaginalis were detected in 70 (6.6%), 6 (0.6%), 12 (1.1%) and 3 (0.3%) women, respectively. The prevalence of C. trachomatis and M. genitalium in the men was 6.5% (10 of 154) and 1.3% (2 of 154). N. gonorrhoeae or T. vaginalis were not detected in any men. In 7 women, multiple agents were found, i.e., C. trachomatis and N. gonorrhoeae (n = 3), C. trachomatis and M. genitalium (n = 2), and M. genitalium and T. vaginalis (n = 1).